The meaning of the NAATA + infinitive construction in basse mandinka - Andrason, Alexander (Lingua Posnaniensis, 2012)
Conclusion: T he author demonstrates that the values displayed by the construction (with an exception of the modal senses) can be connected and a definition, which exceeds a simple inventory of uses, may be provided if one views the locution from a dynamic evolutionary perspective, i.e. as a manifestation of one of the developmental scenarios governing the grammatical evolution of original resultative constructions, namely as a realization of the anterior path. Furthermore, the modal senses of the NAATA form may be related to the anterior trajectory (and to its meanings-stages) if we make use of the evidential path, an evolutionary possibility which links the grammatical life of resultatives with determined modal domains. T his latter proposition, however, needs a more profound analysis and will constitute one of the research activities, conducted by the author in the future.